INTELLECTUAL CAPITAL ON COMPANY PERFORMANCE USING ECONOMIC VALUE ADDED (EVA) METHOD MODERATED BY FIRM SIZE - Persulessy, Grace; Junus, Amiruddin; Darmawati , Darmawati (jfpublisher, 2022)
The company's performance describes various parts of the entire company from financial side to the level of output until the market rate of return. This research aims to examine human capital, capital structure, capital employed on the performance of service companies as measured by using economic value added (EVA). This research used associative research, which has an aim to determine the relationship or influence two or more variables. Quantitative methods are used to examine certain populations or samples, collecting data using research instruments, analyze quantitative or statistical data, within the aim of testing the established hypotheses. Based on the test results, it is proven that the first, second, fifth and sixth hypotheses are not supported by moderating variables. While the third and fourth variables are supported by moderating variables. Based on the results of research and hypothesis testing, it can be concluded that human capital, capital structure has no influence on financial performance as measured by EVA. Moreover, capital employed has an influence on EVA.